Dorsal Thoracic Arachnoid Web and the “Scalpel Sign”: A Distinct Clinical-Radiologic Entity - Reardon, M.A.; Raghavan, P.; Carpenter-Bailey, K.; Mukherjee, S.; Smith, J.S.; Matsumoto, J.A.; Yen, C.-P.; Shaffrey, M.E.; Lee, R.R.; Shaffrey, C.I.; Wintermark, M. (American Journal of Neuroradiology, 2013)
SUMMARY: Arachnoid webs are intradural extramedullary bands of arachnoid tissue that can extend to the pial surface of the spinal cord, causing a focal dorsal indentation of the cord. These webs tend to occur in the upper thoracic spine and may produce a characteristic deformity of the cord that we term the “scalpel sign.” We describe 14 patients whose imaging studies demonstrated the scalpel sign. Ten of 13 patients who underwent MR imaging demonstrated T2WI cord signal-intensity changes, and 7 of these patients also demonstrated syringomyelia adjacent to the level of indentation. Seven patients underwent surgery, with 5 demonstrating an arachnoid web as the cause of the dorsal indentation demonstrated on preoperative imaging. Although the webs themselves are rarely demonstrated on imaging, we propose that the scalpel sign is a reliable indicator of their presence and should prompt consideration of surgical lysis, which is potentially curative.